International legal cooperation of the Eurasian Economic Union with the UN Regional Commissions: modern stage - D. V. Ivanov; M. M. Levina (Московский журнал международного права, 2020)
INTRODUCTION. The article focuses on the analysis of the international legal personality of the Eurasian Economic Union (EAEU) in the context of its international cooperation. Practical implementation of legal possibilities of the interregional interaction is examined on the example of the legal cooperation of the Union with the UN regional commissions, which have recently been incorporated in its foreign policy concept. The authors have also studied the role of the Russian Federation in the process of the practical implementation of the aforementioned track of the Union’s foreign affairs, taking into account Russia’s chairmanship in the EAEU institutions in 2018.MATERIALS AND METHODS. Legal acts related to the EAEU foreign policy strategy, theoretical works of scientists on the international personality of regional integration organizations, offi ally published documents and working materials of the Eurasian Economic Commission form the basis of the present study. Its methodological base consists of such methods of formal logic as analysis, synthesis and induction, along with the use of special methods of the legal analysis required for a comprehensive study, including the formal dogmatic and comparative legal approach.RESEARCH RESULTS. Through the study of the cor-respondence of the EAEU legal nature to the features of an international organization the authors provide legal justification for the scientific approach under which regional integration associations do not differ from “classical” intergovernmental organizations from a formal legal point and, as a result, should be considered as fully-fledged subjects of international law. A comparative analysis of the main tracks of international cooperation of the Union over a five-year period has been carried out with the focus on a detailed study of the legal interaction of the EAEU with the UN regional commissions. Despite the fact that in legal acts relating to the EAEU foreign policy strategy all five regional commissions were enshrined in the category of potential partners, remains obvious the imbalance in the practical implementation of this approach: while the most fruitful international cooperation was actually realized by the Union with the United Nations Economic Commission for Europe, to a much lesser extent – with the Economic and Social Commission for Asia and the Pacific, cooperation with the other three regional commissions is either absent or only at the initial stage. At the same time, the Russian Federation played a leading role in realizing the main goals of the Eurasian integration during its chairmanship in 2018, becoming the flagship in the adoption by the Heads of the Member States of the Union on December 6, 2018 of the Declaration on the further development of integration processes within the Eurasian Economic Union.DISCUSSION AND CONCLUSIONS. With regard to forecasting the prospects for further implementation of the Union’s foreign policy strategy, we shall notice, that, first of all, taking into account the obvious growing international cooperation activity of the EAEU with the UN regional commissions, it seems logical, when forming and adopting subsequent acts defining the directions of the Union’s foreign affairs and international cooperation, to move from considering them into category “potential partners” to the category of international organizations with which it is necessary to develop existing cooperation mechanisms as well as create new ones. In the context of current geopolitical trends, the importance of strengthening further practical cooperation of the EAEU with the UN regional commissions is due to the need for sustainable socioeconomic development of the Eurasian region and the expansion of foreign affairs of the Union, which can be implemented jointly with the UN working bodies through the expert analytical support of common projects, exchange of regulatory experience in a number of areas of economics and social policy, cooperation in the fi ld of technical regulation and standardization.